Experiences of women who use crack - Vania Dias Cruz; Michele Mandagará de Oliveira; Valéria Cristina Christello Coimbra; Luciane Prado Kantorski; Leandro Barbosa de Pinho; Jeane Freitas de Oliveira (Universidade Federal do Ceará, 2014)
This study aimed to understand better the experiences of women who consume crack. It is a qualitative research conducted through a semi-structured interview with 16 women registered in the Estratégia de Redução de Danos de Pelotas/RS [Harm Reduction Strategy of Pelotas/RS/Brazil], in 2012. For data analysis, one used the content analysis, in the modality thematic analysis, from the perspective of gender relations. The results were grouped into two categories: prejudice, prostitution and crime situations and family and friends relationships. One identified women labeled by society as criminals who suffer daily with situations of prejudice, for not having a behavior socially and culturally expected for women, such as being docile and fragile. Adverse events during childhood were identified, however, there was a network of solidarity among people who consume this drug. Based on genders, it can be seen the concrete and symbolic organization of these women's social life and the connections of power in gender relations.